Preparation method of carbon fiber composite material

By using the wetting material of polyamide materials and polymer dispersants, combined with the heating and dispersion treatment and the wetting process at a specific temperature, the problem of poor carbon fiber wetting effect is solved, and the quality uniformity and production efficiency of carbon fiber composite materials are improved. .

CN119465648APending Publication Date: 2025-02-18NANYA PLASTICS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311038889.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2023-08-17
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the existing methods for preparing carbon fiber composite materials, the wetting effect of carbon fiber is poor, resulting in uneven quality of composite materials, and the carbon fiber is prone to stuck in the wetting die head, causing blockage of the production line.

Method used

Polyamide material and polymer dispersant are used as the wetting material, and the polymer dispersant is dispersed by heating the premix to disperse the polymer dispersant to form an wetting material with a viscosity of 10 pascals to 100 pascals seconds, and at 320℃ to 350℃ The carbon fiber is immersed in the wetting material at a temperature.

Benefits of technology

It significantly improves the wetting effect between carbon fiber and the wetting material, ensures that the complete wetting material is attached to the carbon fiber surface, obtains a carbon fiber composite material of uniform quality, and reduces the risk of carbon fiber blocking the die head.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465648A_ABST
    Figure CN119465648A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbon fiber composite material. The method comprises the following steps: providing a premix, wherein the premix comprises a polyamide material and a polymeric dispersant; heating the premix to disperse the polyamide material by the polymeric dispersant so as to form an infiltrated material; at the processing temperature of 320-350 DEG C, carbon fibers are immersed in the infiltrated material, so that the polyamide material dispersed by the polymeric dispersant is attached to the carbon fibers, and the viscosity of the infiltrated material is 10-100 Pascal seconds. And fixing the polyamide material dispersed by the polymeric dispersant on the carbon fiber under a cooling condition to obtain the carbon fiber composite material. In the preparation method of the carbon fiber composite material, the infiltrating material has a good infiltrating effect on the carbon fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for preparing a carbon fiber composite material, and in particular to a method for preparing a carbon fiber composite material suitable for long carbon fibers. Background Art

[0002] Carbon fiber itself has the characteristics of being not easy to deform, highly heat-resistant, high-strength, and highly conductive. The strength of carbon fiber is greater than that of steel, but the density of carbon fiber is less than that of aluminum, so it can be widely used in different fields. Carbon fiber is also often added to composite materials to improve the rigidity of composite materials.

[0003] However, the characteristics of carbon fiber itself can easily cause difficulties in the manufacturing process. For example, when manufacturing carbon fiber composite materials, the carbon fiber is impregnated with plastic, so that the plastic adheres to the surface of the carbon fiber and forms an impregnation layer. Since carbon fiber and plastic are completely different materials, if the impregnation effect of the plastic is not good, it will lead to uneven quality of the composite material, which will negatively affect the quality of the carbon fiber composite material.

[0004] Furthermore, when the carbon fiber surface is not completely attached to the plastic, it is easier to get stuck in the impregnation die, causing the production line to be blocked. Therefore, in order to avoid the problem of carbon fiber getting stuck in the die and causing blockage, it is necessary to reduce the number of carbon fibers impregnated at one time, which will reduce the output of carbon fiber composite materials.

[0005] The existing carbon fiber composite material preparation method has not been able to solve the above-mentioned problem of poor carbon fiber impregnation effect. Therefore, how to improve the plastic impregnation effect on carbon fiber by improving the preparation method and plastic components to overcome the above-mentioned defects has become one of the important issues that this business wants to solve. Summary of the invention

[0006] The technical problem to be solved by the present application is to provide a method for preparing a carbon fiber composite material in view of the deficiencies in the prior art.

[0007] In order to solve the above-mentioned technical problems, one of the technical solutions adopted by the present invention is to provide a method for preparing a carbon fiber composite material. The method for preparing a carbon fiber composite material includes the following steps: providing a premix, the premix comprising a polyamide material and a polymer dispersant. Heating the premix so that the polymer dispersant disperses the polyamide material to form an impregnation. At a processing temperature of 320°C to 350°C, immersing the carbon fiber in the impregnation so that the polyamide material dispersed by the polymer dispersant adheres to the carbon fiber, and the viscosity of the impregnation is 10 Pascal seconds to 100 Pascal seconds. Under cooling conditions, the polyamide material dispersed by the polymer dispersant is fixed on the carbon fiber to obtain a carbon fiber composite material.

[0008] Furthermore, the premix is ​​heated to a temperature in the range of 250° C. to 345° C. to perform a dispersion process.

[0009] Furthermore, the weight average molecular weight of the polymer dispersant is 1000 g / mol to 10000 g / mol.

[0010] Furthermore, the polymer dispersant is a polyolefin type polymer dispersant.

[0011] Furthermore, the relative viscosity of the polyamide material is 2.0 to 4.0.

[0012] Furthermore, before the impregnation treatment, the carbon fiber undergoes a preheating treatment and a yarn spreading treatment, wherein the preheating temperature in the preheating treatment is 110° C. to 130° C.

[0013] Furthermore, the premix further includes a polymer compatibilizer; after the step of immersing the carbon fiber in the impregnation material, the two ends of the polymer compatibilizer are respectively connected to the polyamide material and the carbon fiber dispersed by the polymer dispersant.

[0014] Furthermore, the polymer compatibilizer has maleic anhydride functional groups, and the total weight of monomers for synthesizing the polymer compatibilizer is 100 weight percent, and 0.5 weight percent to 1.3 weight percent of the monomers have maleic anhydride functional groups.

[0015] Furthermore, the premix further comprises a polyolefin elastomer, which is synthesized from monomers selected from the following group: ethylene, 1-propylene, 1-butene, 1-hexene and 1-octene.

[0016] Furthermore, the polyolefin elastomer is selected from the group consisting of ethylene / α-olefin random copolymer, ethylene / α-olefin block copolymer, EPDM elastomer and EPDM elastomer.

[0017] One of the beneficial effects of the present invention is that the method for preparing the carbon fiber composite material provided by the present invention can improve the wetting effect of the impregnating material on the carbon fiber through the technical scheme of "heating the premix to allow the polymer dispersant to disperse the polyamide material to form a impregnating material" and "the viscosity of the impregnating material is 10 Pascal seconds to 100 Pascal seconds".

[0018] To further understand the features and technical contents of the present application, please refer to the following detailed description and drawings of the present application. However, the drawings provided are only for reference and illustration and are not intended to limit the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The present invention is a flowchart of the steps of the method for preparing the carbon fiber composite material.

[0020] Figure 2 Schematic diagram of equipment for preparing the carbon fiber composite material of the present invention. DETAILED DESCRIPTION

[0021] The following is an explanation of the implementation method of the "method for preparing carbon fiber composite materials" disclosed in the present invention through specific examples. Those skilled in the art can understand the advantages and effects of the present invention from the contents disclosed in this specification. The present invention can be implemented or applied through other different specific embodiments, and the details in this specification can also be modified and changed in various ways based on different viewpoints and applications without departing from the concept of the present invention. In addition, the drawings of the present invention are only simple schematic illustrations and are not depicted in actual size. It is stated in advance. The following implementation methods will further explain the relevant technical content of the present invention in detail, but the disclosed content is not intended to limit the scope of protection of the present invention. In addition, the term "or" used in this article may include any one or more combinations of the associated listed items depending on the actual situation.

[0022] In order to improve the wetting effect between the carbon fiber and the impregnation material, the present invention selects polyamide material and polymer dispersant as the impregnation material. The polyamide material can improve the wetting effect of the impregnation material on the carbon fiber under the dispersion treatment of the polymer dispersant. When the impregnation effect is improved, the carbon fiber surface can be completely attached to the impregnation material, and a carbon fiber composite material with uniform quality can be obtained. In addition, during the preparation process, it is less likely to cause the problem of carbon fiber blocking the die head.

[0023] See also Figure 1 As shown, the method for preparing the carbon fiber composite material of the present invention comprises the following steps.

[0024] In step S1 , a premix is ​​provided, which includes a polyamide material and a polymer dispersant.

[0025] Polyamide materials have the characteristics of high strength and high durability. When polyamide materials are used as the impregnation material of carbon fibers, the strength of carbon fibers can be further improved. Therefore, compared with pure carbon fiber materials, the carbon fiber composite material of the present invention has higher strength and can be used as raw materials for military products or automobiles and motorcycles. In addition, the surface of polyamide materials has a large number of hydrophilic amide groups, which is conducive to subsequent other surface treatment processes.

[0026] After comprehensively considering the characteristics and processability of the carbon fiber composite material, the relative viscosity of the polyamide material is 2.0 to 4.0, for example, the relative viscosity of the polyamide material can be 2.3, 2.6, 2.9, 3.2, 3.5 or 3.8. However, the present invention is not limited thereto. In an exemplary embodiment, a polymer (nylon 66) formed by condensation copolymerization of hexamethylenediamine and adipic acid or polycaprolactam (nylon 6) can be selected as the polyamide material.

[0027] The addition of polymer dispersants can make the polyamide material adhere well to the carbon fiber, thereby improving the wetting effect of the sizing material on the carbon fiber. Since the melting point of the polyamide material is relatively high (about 280°C), in order to cope with various high-temperature processing steps in the subsequent manufacturing process, the present invention uses a polymer dispersant with a higher boiling point to avoid the polymer dispersant evaporating during the processing step and losing the effect of dispersing the polyamide material.

[0028] In an exemplary embodiment, the polymer dispersant is a polyolefin polymer dispersant. The weight average molecular weight of the polymer dispersant is 1000 g / mol to 10000 g / mol, for example, 2000 g / mol, 3000 g / mol, 4000 g / mol, 5000 g / mol, 6000 g / mol, 7000 g / mol, 8000 g / mol or 9000 g / mol.

[0029] In this molecular weight range, the polymer dispersant can more evenly disperse the polyamide material to achieve the desired dispersion effect. In addition, the polyamide material in the above molecular weight range can have a better dispersion effect with the polymer dispersant in the above molecular weight range.

[0030] In step S2, the premix is ​​heated to allow the polymer dispersant to disperse the polyamide material to form a wetted material.

[0031] During the dispersion process, the premix can be heated to a temperature range of 250°C to 345°C. Under the high temperature environment (250°C to 345°C), the polymer dispersant and the polyamide material will be rearranged due to the energy obtained. In terms of microstructure, the polymer dispersant will surround the polyamide material and evenly disperse the polyamide material into multiple molecular clusters. The multiple molecular clusters are stable and will not re-agglomerate.

[0032] Specifically, the method of heating the premix for dispersion treatment is to use a twin-screw extruder. First, the premix is ​​put into the twin-screw extruder, and the twin-screw extruder is set to extrude at a speed of 220 rpm to 270 rpm and a temperature of 250°C to 345°C, and a wetted material can be obtained. For example, the temperature of heating and mixing the polyamide material and the polymer dispersant can be 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C or 340°C.

[0033] In an exemplary embodiment, the sizing material may also selectively include a polymer compatibility agent. The addition of the polymer compatibility agent may increase the compatibility between the polyamide material and the carbon fiber, and may further enhance the wetting effect between the carbon fiber and the sizing material.

[0034] Specifically, the two ends of the polymer compatibilizer can be connected to the polyamide material (molecular group) and the carbon fiber respectively, so the wetting effect between the carbon fiber and the sizing material can be improved. In the presence of the polymer dispersant, the polyamide material has been evenly dispersed into multiple molecular groups, and the two ends of the polymer compatibilizer can easily connect the molecular group and the carbon fiber. Therefore, the addition of the polymer compatibilizer can improve the compatibility between the polyamide material and the carbon fiber, thereby improving the wetting effect. Moreover, this wetting effect cannot be achieved by only adding the polymer dispersant or only adding the polymer compatibilizer.

[0035] In an exemplary embodiment, the polymer compatibilizer may have a maleic anhydride functional group, and the maleic anhydride functional group may be connected to the polyamide material (molecular group) to enhance the compatibility between the polyamide material and the carbon fiber.

[0036] Taking the total weight of monomers for synthesizing the polymer compatibility agent as 100 weight percent, 0.5 weight percent to 1.3 weight percent of the monomers have maleic anhydride functional groups. For example, the content of monomers having maleic anhydride functional groups can be 0.6 weight percent, 0.7 weight percent, 0.8 weight percent, 0.9 weight percent, 1.0 weight percent, 1.1 weight percent or 1.2 weight percent. In other words, the grafting rate of maleic anhydride functional groups in the polymer compatibility agent is 0.5% to 1.3%.

[0037] In an exemplary embodiment, the polymer compatibilizer can be a polyolefin elastomer with maleic anhydride functional groups (POE-g-MAH) or polypropylene with maleic anhydride functional groups (PP-g-MAH). Preferably, the polymer compatibilizer is polypropylene with maleic anhydride functional groups.

[0038] In an exemplary embodiment, polyolefin elastomers may be selectively added to the sizing material. The addition of polyolefin elastomers can improve the toughness of carbon fiber composite materials, especially the toughness in low temperature environments. Compared with polyolefin plastics, polyolefin elastomer molecules have higher elongation and resilience at room temperature, are less likely to permanently deform or break after being stressed, and have lower density.

[0039] The monomers for synthesizing the polyolefin elastomer are selected from the group consisting of ethylene, 1-propylene, 1-butene, 1-hexene and 1-octene. In an exemplary embodiment, the polyolefin elastomer is selected from the group consisting of ethylene / α-olefin random copolymer, ethylene / α-olefin block copolymer, ethylene propylene rubber (EPM) and ethylene propylene diene monomer (EPDM).

[0040] In step S3, the carbon fiber undergoes a preheating treatment and a yarn spreading treatment. The preheated and spread carbon fiber can have a higher strength, so as to have a better impregnation effect in the next step. The temperature of the preheating treatment can be 110° C. to 130° C., but the present invention is not limited thereto.

[0041] In an exemplary embodiment, a long carbon fiber with a weight of 800 g / 1000 m to 2000 g / 1000 m can be used. Preferably, a long carbon fiber with a weight of 1500 g / 1000 m to 1800 g / 1000 m can also be used. The tensile strength of the carbon fiber is 4500 MPa to 5200 MPa. The tensile modulus of the carbon fiber is 200 GPa to 300 GPa. The elongation of the carbon fiber is 1% to 3%. The density of the carbon fiber is 1.5 g / cm3 to 2.0 g / cm3. The diameter of the carbon fiber is 5 microns to 10 microns.

[0042] In step S4, the carbon fibers are immersed in a sizing material at a processing temperature of 320° C. to 350° C., so that the polyamide material dispersed by the polymer dispersant can be attached to the carbon fibers.

[0043] Polyamide material is a macromolecule and generally has a high viscosity in the absence of solvent. In order to achieve a good wetting effect, the viscosity of the wetting material is controlled to be 10 Pa·s to 100 Pa·s.

[0044] In order to reduce the viscosity of the impregnation material, in step S1, a polymer dispersant is used to disperse the polyamide material to form a plurality of molecular clusters, which can achieve the effect of reducing the viscosity of the polyamide material, and a polymer compatibility agent can be further added. In addition, in step S2, using a higher processing temperature is also conducive to reducing the viscosity of the polyamide material.

[0045] In other words, adding polymer dispersants (and polymer compatibilizers) and adjusting the processing temperature (320°C or 350°C) can reduce the viscosity of the polyamide material and enhance the wetting effect between the carbon fiber and the impregnating material.

[0046] In the present invention, the viscosity of the impregnation material may also be 20 Pascal seconds, 30 Pascal seconds, 40 Pascal seconds, 50 Pascal seconds, 60 Pascal seconds, 70 Pascal seconds, 80 Pascal seconds or 90 Pascal seconds. However, the present invention is not limited thereto.

[0047] When the wetting effect between the carbon fiber and the impregnation material is further improved, the impregnation material can adhere to the surface of the carbon fiber and form an impregnation film with uniform thickness. In the past, in order to avoid that part of the carbon fiber surface is not attached to the impregnation liquid, the manufacturing process parameters are adjusted to form a thicker impregnation film on the carbon fiber surface. When the impregnation effect is improved, the impregnation material can easily adhere to the carbon fiber surface and form an impregnation film, and it is no longer necessary to form such a thick impregnation film on the carbon fiber surface. Therefore, in the present invention, the parameters can be adjusted to form a thinner impregnation film on the carbon fiber surface, and the problem of part of the carbon fiber surface not being attached to the impregnation liquid will not occur.

[0048] The thickness of the above impregnation film can be quantified as the proportion of carbon fiber in the carbon fiber composite material. The thicker the impregnation film, the lower the content of carbon fiber in the carbon fiber composite material. The thinner the impregnation film, the higher the content of carbon fiber in the carbon fiber composite material.

[0049] In step S5, under cooling conditions, the polyamide material dispersed with a polymer dispersant is fixed on the carbon fiber to obtain a carbon fiber composite material.

[0050] After cooling, the molecular clusters formed by the polymer dispersant and the polyamide material can be fixed on the surface of the carbon fiber to form a carbon fiber composite material. The carbon fiber composite material of the present invention has high strength characteristics and a hydrophilic surface that is beneficial to subsequent other surface treatment processes.

[0051] The weight of the carbon fiber composite material is compared with the specifications of the original carbon fiber, and then the content ratio of the carbon fiber composite material can be calculated according to the formulation ratio of the impregnated material. Taking the total weight of the carbon fiber composite material as 100 weight percent, the content of the carbon fiber is 15 weight percent to 55 weight percent, the content of the polyamide material is 40 weight percent to 80 weight percent, the content of the polymer dispersant is 0.5 weight percent to 2 weight percent, the content of the polymer compatibilizer is 1 weight percent to 10 weight percent, and the content of the polyolefin elastomer is 1 weight percent to 10 weight percent.

[0052] In addition to the above ingredients, antioxidants and lubricants may be optionally added to the raw material mixture. Taking the total weight of the carbon fiber composite material as 100 weight percent, the content of the antioxidant is 0.1 weight percent to 2 weight percent, and the content of the lubricant is 0.1 weight percent to 2 weight percent.

[0053] In step S6, the carbon fiber composite material is pelletized to form carbon fiber composite pellets. Specifically, the carbon fiber composite pellets have a diameter of 3 mm and a length of 11 mm.

[0054] See also Figure 2 As shown, Figure 2 Schematic diagram of equipment for preparing the carbon fiber composite material of the present invention. In order to prepare the carbon fiber composite material, the aforementioned impregnation material is put into a twin-screw extruder 10, and the temperature of the twin-screw extruder 10 is set to 250° C. to 345° C. and the screw speed is 250 rpm. Therefore, the polyamide material and the polymer dispersant can be uniformly mixed in a molten state, so that the polymer dispersant disperses the polyamide material. After the impregnation material is formed, the impregnation material is transported to an impregnation device 20.

[0055] The rolled continuous carbon fiber F (Formosa Carbon Fiber, model: TC-36P 24K) is preheated at 120°C and conveyed to the impregnation device 20 after yarn spreading. After impregnation, the surface of the carbon fiber F is completely covered with the impregnation material. After the carbon fiber F passes through the cooling and shaping device 30, it is conveyed to the pelletizer 40, and carbon fiber composite pellets are produced by the pelletizer 40. Specifically, the carbon fiber composite pellets have a diameter of 3 mm and a length of 11 mm, but the present invention is not limited thereto.

[0056] In order to verify that the carbon fiber composite material of the present invention has good physical strength, the carbon fiber composite materials of Examples 1 to 4 and Comparative Examples 1 to 2 were prepared according to the above method and their properties were tested. The main difference between Examples 1 to 4 and Comparative Examples 1 to 2 is that different fibers were used for impregnation, while Comparative Examples 1 to 2 used glass fibers for impregnation.

[0057] The specific components of the carbon fiber composite materials of Examples 1 to 4 and Comparative Examples 1 to 2 are listed in Table 1, and the content of each component in Table 1 is expressed in parts by weight. In Examples 1 to 4 and Comparative Examples 1 to 2, the polyamide material can be nylon 6 (hereinafter referred to as PA6) with a relative viscosity of 2.46 or nylon 66 (hereinafter referred to as PA66) with a relative viscosity of 2.7. The polymer dispersant is a polyolefin-type hyperdispersant (also known as a polyolefin-type polymer dispersant) with a weight-average molecular weight of 1000 g / mol to 10000 g / mol. The polymer compatibility agent is polypropylene with maleic anhydride functional groups. The melting index of the polyolefin elastomer is 8 g / 10 min. The model of the antioxidant is B1171. The lubricant is polyethylene wax.

[0058] The tensile strength and elongation of carbon fiber composites are analyzed according to ISO 527. The tensile modulus of carbon fiber composites is analyzed according to ISO 527. The flexural strength of carbon fiber composites is analyzed according to ISO 178. The flexural modulus / modulus of carbon fiber composites is analyzed according to ISO 178. The impact strength of carbon fiber composites is analyzed according to ISO 178 and measured at 23°C and -40°C. The heat deformation temperature of carbon fiber composites is analyzed according to ISO 178. The flow length of carbon fiber composites is analyzed according to ASTM D3123.

[0059] Table 1

[0060]

[0061]

[0062] From the results in Table 1, it can be seen that the preparation method of the carbon fiber composite material of the present invention can improve the wetting effect of the impregnating material on the carbon fiber and overcome the problem that the carbon fiber will block the die head in the past. After improving the wetting effect, a thinner impregnation layer can be formed on the surface of the carbon fiber to increase the proportion of the carbon fiber component in the carbon fiber composite material.

[0063] The carbon fiber composite material of the present invention has the advantage of high carbon fiber content, so that the carbon fiber composite material can have good tensile strength and flexural strength. Specifically, with the total weight of the carbon fiber composite material as 100 weight percent, the carbon fiber content can be as high as 40 weight percent or more, preferably 45 weight percent or more, for example: the carbon fiber content is 45 weight percent to 55 weight percent. Compared with the glass fiber composite material (Comparative Examples 1 and 2), the carbon fiber composite material of the present invention has good tensile strength and flexural strength.

[0064] Please compare Examples 1 and 2 with Examples 3 and 4. When more polyolefin elastomer is added, the elongation, bending elastic modulus and impact strength of the carbon fiber composite material can be improved. Taking the total weight of the carbon fiber composite material as 100 weight percent, the content of the polyolefin elastomer is 4 weight percent to 8 weight percent.

[0065] Please compare Examples 1 and 3 with Examples 2 and 4. When nylon 66 is selected as the polyamide material, the tensile strength, impact strength and heat deformation temperature of the carbon fiber composite material can be improved.

[0066] [Beneficial Effects of Embodiments]

[0067] One of the beneficial effects of the present invention is that the method for preparing the carbon fiber composite material provided by the present invention can improve the wetting effect of the impregnating material on the carbon fiber through the technical scheme of "heating the premix to allow the polymer dispersant to disperse the polyamide material to form a impregnating material" and "the viscosity of the impregnating material is 10 Pascal seconds to 100 Pascal seconds".

[0068] Furthermore, in order to improve the wetting effect of the sizing material on the carbon fiber, the present invention adds a polymer dispersant and performs a dispersion treatment at a temperature of 250°C to 345°C. In the step of heating the premix, the molecules of the polymer dispersant and the polyamide material will be rearranged. In terms of microstructure, the polyamide material will be evenly dispersed into multiple molecular clusters by the polymer dispersant and will not re-agglomerate. When the polyamide material is dispersed by the polymer dispersant, the wetting effect of the sizing material on the carbon fiber can be improved.

[0069] In order to improve the dispersing effect on the polyamide material, the present invention can select 1000 g / mol to 10000 g / mol of polymer dispersant to evenly disperse the polyamide material into molecular clusters of appropriate size to prevent the molecular clusters from agglomerating again during the processing. In addition, the molecular weight can be controlled to achieve the effect of adjusting the boiling point of the polymer dispersant to avoid the evaporation of the polymer dispersant in the high temperature step. After testing, it was found that when the polymer dispersant is a polyolefin polymer dispersant, it has a better dispersing effect. In addition, a specific molecular weight can be used with a polyamide material to form a stable molecular cluster.

[0070] Furthermore, a polymer compatibilizer can be further added to the premix. The polymer compatibilizer can enhance the wetting effect between the polyamide material and the carbon fiber. When the polyamide material is dispersed to form multiple molecular clusters, the addition of the polymer compatibilizer can further exert its effect and significantly enhance the wetting effect between the polyamide material and the carbon fiber.

[0071] In the present invention, a polymer compatibilizer having a maleic anhydride functional group is further selected, and the maleic anhydride functional group can enable the two ends of the polymer compatibilizer to be connected to the polyamide material and the carbon fiber respectively. By adjusting the content of the maleic anhydride functional group, the wetting effect between the polyamide material and the carbon fiber can be further improved.

[0072] The contents disclosed above are only preferred feasible embodiments of the present application, and are not intended to limit the protection scope of the claims of the present application. Therefore, all equivalent technical changes made using the contents of the present application specification and drawings are included in the protection scope of the claims of the present application.

Claims

1. A method for preparing a carbon fiber composite material, characterized in that: The preparation method of the carbon fiber composite material comprises: Providing a premix comprising a polyamide material and a polymer dispersant; Heating the premix so that the polymer dispersant disperses the polyamide material to form a wetted material; At a processing temperature of 320° C. to 350° C., immersing the carbon fiber in the sizing material so that the polyamide material dispersed by the polymer dispersant is attached to the carbon fiber, and the viscosity of the sizing material is 10 Pascal seconds to 100 Pascal seconds; and Under cooling conditions, the polyamide material dispersed by the polymer dispersant is fixed on the carbon fiber to obtain a carbon fiber composite material.

2. The preparation method according to claim 1, characterized in that: The premix is ​​heated to a temperature in the range of 250° C. to 345° C. to perform the dispersion treatment.

3. The preparation method according to claim 1, characterized in that: The weight average molecular weight of the polymer dispersant is 1000 g / mol to 10000 g / mol.

4. The preparation method according to claim 1, characterized in that: The polymer dispersant is a polyolefin polymer dispersant.

5. The preparation method according to claim 1, characterized in that: The relative viscosity of the polyamide material is 2.0 to 4.

0.

6. The preparation method according to claim 1, characterized in that: Before the impregnation treatment, the carbon fiber undergoes a preheating treatment and a yarn spreading treatment, wherein the preheating temperature in the preheating treatment is 110° C. to 130° C.

7. The preparation method according to claim 1, characterized in that: The premix further includes a polymer compatibilizer; after the step of immersing the carbon fiber in the sizing material, the two ends of the polymer compatibilizer are respectively connected to the polyamide material and the carbon fiber dispersed by the polymer dispersant.

8. The preparation method according to claim 7, characterized in that: The polymer compatibilizer has maleic anhydride functional groups. The total weight of monomers used to synthesize the polymer compatibilizer is 100 weight percent, and 0.5 weight percent to 1.3 weight percent of the monomers have maleic anhydride functional groups.

9. The preparation method according to claim 1, characterized in that: The premix further includes a polyolefin elastomer, which is synthesized from monomers selected from the following group: ethylene, 1-propylene, 1-butene, 1-hexene and 1-octene.

10. The preparation method according to claim 9, characterized in that: The polyolefin elastomer is selected from the group consisting of: ethylene / α-olefin random copolymer, ethylene / α-olefin block copolymer, ethylene propylene diene monomer rubber elastomer and ethylene propylene diene monomer rubber elastomer.